Managing disaster risks to cultural heritage from risk preparedness to recovery for immovable heritage - Romão, Xavier; Rouhani, Bijan (London Routledge, Taylor & Francis Group, 2024)
"Managing Disaster Risks to Cultural Heritage presents case studies from different regions in the world and establishes a framework for understanding, identifying, and analysing disaster risks to immovable cultural heritage. Including contributions from academics and practitioners from around the globe, the book presents a comprehensive view of the scholarship relating to cultural heritage, disaster risk preparedness and post-disaster recovery. Particular attention is given to the complex and dynamic nature of disaster risks and how they evolve during different phases of a catastrophic event, especially as hazards can create secondary effects that have greater impacts on cultural heritage, infrastructure, and economy. Arguing that risk preparedness and mitigation have historically been secondary to reactive emergency and first aid response, the book demonstrates that preparedness plans based on sound risk assessments can prevent hazards from becoming disasters. Emphasising that the protection of cultural heritage through preparedness and mitigation actions and risk adaptation measures, especially for climate change, can contribute to the resilience of societies, the book highlights the vital role of communities in such activities. Managing Disaster Risks to Cultural Heritage will be useful to students, professionals, and scholars studying and working with cultural heritage protection. It will be of particular interest to those working in the Cultural Heritage, Archaeology, Conservation and Preservation, Sustainable Development and Disaster Studies fields"--
Understanding Risks to Cultural Heritage : Are Disasters Natural? / Francesco De Pascale -- Disasters and Heritage Loss / Xavier Romão and Esmeralda Paupério -- Stability of Cultural Information in Unstable Environments : Data Management for Digital Preservation of Immovable Cultural Heritage against Natural Hazards / Michael T. Fisher -- Disaster Risk Assessment Strategies for Cultural Heritage / Xavier Romão and Bijan Rouhani -- From Risk Reduction to Risk Adaptation : Protecting the Past for the Future / Rohit Jigyasu and Jukka Jokilehto -- Remote Sensing and Disaster Risk Management for Cultural Heritage / Louise Rayne, Bijan Rouhani, and Jen Lavris Makovics -- Can Our Past Save Our Future? Traditional Knowledge and Disaster Risk Management for Cultural Heritage / Rohit Jigyasu and Jukka Jokilehto -- Emergency Response to Cultural Heritage / Bijan Rouhani and Xavier Romão -- Cultural Heritage Recovery and Reconstruction / Jukka Jokilehto -- Surviving Disasters : Traditional Disaster-Resilient Designs in Japan / Takeyuki Okubo -- A Case Study from the World Heritage Site of the Tabriz Historic Bazaar and Fire Management, Iran / Farhad Nazari and Mohammad Aminian -- Winds, Rain and Thunder : Hurricanes, Community Support, and Preparedness at Teyuna-Ciudad Perdida Archaeological Park, Colombia, a Case Study / Santiago Giraldo -- Counting the Cost : Architectural Heritage in Post-Quake Christchurch, 2010-2020 / Ian Lochhead -- A Multilevel Framework for Flood Risk Assessment of Cultural Heritage : A Case Study from Portugal / Rui Figueiredo, Xavier Romão, and Esmeralda Paupério -- Leveraging Digital Systems for Disaster Management at the UNESCO World Heritage Site of Bagan Archaeological Zone in Myanmar / Tharaphy Aung and Arun Menon.
Includes bibliographical references and index.
Keywords: Emergency management -- Case studies; Hazard mitigation -- Case studies; Cultural property -- Protection -- Case studies